Pengaruh Kinerja Dewan Pengawas Syariah KSPPS Kota Padang Dalam Mewujudkan Kepatuhan Syariah - Afriyanti, Afriyanti; Fitri, Radia; Ruswandi, Ruswandi (ITB AAS INDONESIA Surakarta, 2024)
Sharia Compliance in Islamic Financial Institutions is compliance, fulfilment of basic values and absolute prices. As an institution that carries the name sharia, KSPPS is expected to provide a better understanding for the general public directly, because its role is closer to the community. This study aims to determine the extent to which the performance of DPS will affect the course of the development of KSPPS in the village. Qualitative descriptive research method. The data collection techniques used were documentation studies, in-depth interviews, analysis was done by narrating the results of interviews, which were then processed again by the author. The result of this research is that sharia compliance has not been fulfilled in the performance of DPS in KSPPS Padang City. The author found that the appointment of DPS is only seen from the point of view of the community store around KSPPS or the village alone, besides that there is also concurrent work so that there is also no standard procedure from the institution on the performance of the DPS. The selected DPS should have integral scientific qualifications, namely understanding the science of muamalah fiqh, sharia and modern Islamic financial economics. It is not the qualifications of all majors.